# 12-23c=7(9-c)

*print*Print*list*Cite

### 5 Answers

12 - 23**c** = 7 (9 - **c**)

Let's start by solving the bracket on RHS:

`=>` 12 - 23**c** = (7X9) - 7**c**

`=>` 12 - 23**c** = 63 - 7**c**

Regrouping parts of the equation:

`=>` -23c + 7**c** = 63 - 12

Solving for **c**:

`=>` -16**c** = 51

`=>` **c** = -51/16

Hence, the value of **c **is -51/16.

Solve 12-23c=7(9-c):

12-23c=7(9-c) Eliminate the parantheses using the distributive property

12-23c=63-7c Add 23c to both sides; subtract 63 from both sides

-51=16c Divide both sides by 16

`c=-51/16=-3.1875`

----------------------------------------------------------------

The solution is `c=-51/16=-3.1875`

---------------------------------------------------------------

I assume you want to solve the above equation for c. See the work below:

12-23c=7(9-c) multiply the seven out on the right side:

12-23c=63-7c add 23c to both sides to isolate the variable:

12=63-7c+23c=63+16c subtract 63 from both sides:

12-63=-51=16c divide both sides by 16:

**c=-51/16=-3.1875**

12 - 23c = 7 (9-c)

First distribute the 7 on the left side

By distributing, you should get

12 - 23c = 63 - 7c now add 7 on both sides

By adding, you should get

12 - 16c = 63 now subtract 12 on both sides

By subtracting, you should get

-16c = 51 now divide -16 on both sides

By dividing, you should get

C = -51/16 which is your answer

This is the equation you should solve.

12-23c=7(9-c) you should distribute 7 from the 9 and -c.

12-23c=63-7c

-12 -12

-23c=51-7c

+7c +7c

-16c=51

/-16 /-16

**c=-3.1875 So the answer is -3.1875.**